Identifikasi Kriteria Keberhasilan Proyek - Mila Faila Sufa (Performa: Media Ilmiah Teknik Industri, 2012)
The successful completion of project requires effective management of the multiple barriers faced by the parties involved. The basic concept of project success is ambiguous because of the varying perceptions of the different parties involved in the construction and the owner, architects,contractors and surveyors as well as experts. This study aims to identify the criteria for project success from the desire of stakeholders involved and the achievement of goals of the project. Definition of success is often changed from one project to another. It also depends on your point of view different from the individuals involved and the objectives to be achieved and associated with several elements such as technical, financial,educational, social and professional issues.